Protective effects of Citrullus vulgaris on Irradiated Lymphocyte Sub-membrane - Khairul Osman; Norashikin Md Saad; Ezlan Elias; Siti Fatimah Ibrahim; Jamaludin Mohamed; Proom Proomwichit (penerbit ukm, 2005)
A study was conducted to determine the radioprotective effects of Citrullus vulgaris on the lymphocyte sub-membrane particularly the actin layer. A total of 30 adult male Sprague-Dawley rats were divided into three equal groups of positive control, negative control and treatment. The positive and negative control groups were force fed with 40 ml/kg body weight of normal saline while the treatment group received 40 g/kg body weight of fresh juice of C. vulgaris daily. After a week the positive control and treatment groups were irradiated with 90 rad gamma radiation. Viable lymphocytes were determined using propidium iodine and acridine orange stain and observed under a fluorescent microscope. The percentage of viable lymphocytes of the treatment group(71.0%; p = 0.03) was significantly higher than the positive control group. The results showed that C. vulgaris possessed radioprotective effects because the lymphocyte actin was not damaged. The radioprotection effects could be due to the presence of antioxidants in C. vulgaris.